The interplay between historical trauma, substance use disorders, appetitive aggression and the link with violent crime among young male adults in conflict with the law in South Africa - Whiting, Sean (Department of Social Development, 2024)
The study investigated the interplay between trauma, substance use disorders (SUDs) and appetitive aggression and its links to violent crime among a cohort of 159 young male adults (aged 25 to 34) incarcerated at George Correctional Centre in the Garden Route District in the Western Cape Province. The context of why there are high rates of violent crime in South Africa relates to various correlates, including underlying structural factors – that provide the contextual basis of the study. The cycle of violence theory provides the conceptual and theoretical framework. This dissertation hypothesises that trauma, in the form of adverse childhood experiences and adverse adult experiences, is central to male victimisation, while SUDs and appetitive aggression serve to exacerbate young males' propensity to violent crime. The assumption is that male victimisation perpetuates the cycle of violent crime in South Africa – along with other correlates. This cross-sectional study is a quantitative examination of particular predictors that predispose young adults to violent crime in South Africa. The study utilised a semistructured Survey Questionnaire. Data was collected in a classroom set-up by the Researcher assisted by Correctional Services' staff officials. Psychological measurement scales previously tested for reliability and validity were used in the questionnaire instrument. These included: Scale for Historical Trauma exposure; Scale for SUD); and Scale for Appetitive Aggression. Data analysis proceeded using SPSS software, incorporating descriptive and inferential analysis. Pearson's correlations of bivariate predictor and outcome variables provided significance measures for hypothesis tests to answer questions 1 – 3. Multiple linear regression tests (t-tests) provided the data to answer the primary question of the study: Is there interplay between trauma, substance use disorders and appetitive aggression and violent crime? The main findings of the study are that ACEs (adverse childhood experiences) and adverse adult experiences is central to male victimisation and violent crime and that SUD and appetitive aggression ‘makes a bad situation worse'. The primary limitation of the study was that the sample was too small to make significant relational findings of the multivariate variables. Recommendations include that similar, national v longitudinal studies be done with larger samples – to produce improved findings and to better understand male victimisation and violent crime offending as predictors of the cycle of violence in South Africa. The Significance of the study includes inter alia to add to the body of knowledge of a broader understanding of the correlates and the interplay of predictors that perpetuate the cycle of violent crime in South Africa.